2002
DOI: 10.1002/yea.835.abs
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive response of Saccharomyces cerevisiae to mercury exposure

Abstract: The budding yeast Saccharomyces cerevisiae has been shown to possess a number of discrete but overlapping adaptive stress responses. We show here that yeast has an adaptive stress response towards mercury and that this response overlaps to some extent with the H 2 O 2 and cadmium-inducible stress responses. Expression of the yeast GSH1 gene, encoding c-glutamylcysteine synthetase, is known to be regulated by hydrogen peroxide; in this study we show that expression of a GSH1-lacZ reporter gene is shown to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
3
14
0
1
Order By: Relevance
“…4A), although the detection range for As was limited compared to that for Cd. Several studies reported that pathways for As and Hg detoxification in S. cerevisiae are similar to those for Cd detoxification (11,14,40,47), which is consistent with our observation that the ScSEO1 promoter is highly induced not only by Cd but also by As and Hg. The negligible response of the HpSEO1 promoter to Hg suggests that H. polymorpha has similar detoxification responses for As and Cd but uses a different defense mechanism against Hg toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…4A), although the detection range for As was limited compared to that for Cd. Several studies reported that pathways for As and Hg detoxification in S. cerevisiae are similar to those for Cd detoxification (11,14,40,47), which is consistent with our observation that the ScSEO1 promoter is highly induced not only by Cd but also by As and Hg. The negligible response of the HpSEO1 promoter to Hg suggests that H. polymorpha has similar detoxification responses for As and Cd but uses a different defense mechanism against Hg toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the oxidative stress produced by mercury exposure is similar to that produced by treatment with hydrogen peroxide, consistent with the finding that Yap1 is also involved in the response of yeast towards mercury (Westwater et al, 2002). Exposure to the excessive amounts of heavy metals 344 • Choi et al…”
Section: Discussionsupporting
confidence: 69%
“…Mitigation of endogenous mercury depends as a part on the presence of antioxidants such as GSH -most abundant intracellular nonprotein thiol that plays a central role in the maintenance of cellular redox status by quenching free radicals generated during oxidative stress (Jan et al, 2011). Expression of the gene encoding γ-glutamylcysteine synthetase is regulated by mercury and cadmium, but not other redox-active metals, including copper and iron, and its mercury-mediated regulation is not by the same mechanism used by cadmium (Westwater et al, 2002).…”
Section: 미생물학회지 제51권 제4호mentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, Yap1p and Skn7p regulators do not always act together and have some independent specialized functions [32,56,59]. Yap1p is also involved in heavy metal, diamide and diethylmaleate tolerance, whereas Skn7p is important for cell wall biosynthesis, cell cycle regulation and adaptation to osmotic stress [56,[60][61][62]. However, the functions of most genes regulated by Skn7p are still unknown [32,56].…”
Section: Regulation Of Global Responsementioning
confidence: 99%